PENURUNAN HIDROGRAF SATUAN TANPA DATA HUJAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
A design flood is very important information of hydrology in sizing various hydraulic structures. It can be obtained from several existing methods. One of widely used method and proved giving a good result in predicting a design flood is unit hydrograph method (UH). Conventionally, UN can be easily derived if hydrograph data and callsath'e rainfall are available. But in practice, to derive an UH is lIot easy task. A number of problem emerges, attributable to availability of observed automatic rainfall data and the influence of initial soil moisture conditions. This condition can trigger an underestimated or overestimated design floods. A new approach of UH development to overcome this problem is needed by using discharge data only (UH IER). The advantage in using discharge data is that all processes in river basin have been accommodated in discharge data including variability of rainfall. The derivation of UH IER will be tested in six selected catchments at Cimanuk river basin. The analysis starts with separating total hydrograph into two components i.e. baseflow and direct runoff by applying filter separation autoregressive method. Inversely estimated rainfall (IER) of recession part of the direct runoff is then applied. Based on the resulted IER and the direct run off Collins method is used for deriving its unit hydrograph. To compare the results, UH also derived by using automatic rainfall data where effective rainfall is computed using runoff coefficient (UH ARR-f) and &#510